STRATEGIES AND IMPLEMENTATION OF DEVELOPMENT OF FUTURE COCONUT PRODUCTS - LAY, ABNER; PASANG, PATRIK M. (Puslitbang Perkebunan, 2012)
In line with problems, alternative solutions, and issues on national coconut, as well as the determinants factors on development, it is required practical strategy that can be implemented to gain success in future coconut product development. The development strategy may consist of the direction, goals, objectives, priorities, and development phases. Implementation includes the optimalization of farming, development and marketing products. Improvement of coconut products, that can be executed massively to the farmers group level and industry for local/domestic market, are young coconut products, coconut coktail, coconut jam, baby food supplements, soft drinks, nata de coco, coconut water sauce, coconut flour, virgin coconut oil, coconut shell charcoal, charcoal briquette, liquid smoke of coconut shell, coconut wood, and organic fertilizer. While the exporting goods are such as copra, white copra, raw coconut oil, coconut cake, desiccated coconut, and active charcoal. Â Key words:Â Coconut, farm business, industry, product diversification, farmers group